Perlindungan Hukum Terhadap Saksi Pelapor (Whistleblower) Dalam Kasus Tindak Pidana Korupsi di Indonesia - Komang Ayu Trisna Dewi; Anak Agung Sagung Laksmi Dewi; Made Minggu Widiantara (Jurnal Analogi Hukum, 2025)
The title of this research is Legal Protection of Whistleblower Witnesses in Corruption Crimes Cases in Indonesia. The problems are (1) How is the legal regulation of whistleblower witnesses in corruption cases in Indonesia? (2) How is the legal protection of whistleblower witnesses in corruption cases in Indonesia? This research conducts a normative legal study using statutory and conceptual techniques. Primary, secondary, and tertiary online documents are the legal resources used. Descriptive-analytical techniques are used to evaluate legal materials. Legislation No. 31/2014 regulates the prerequisites for parties seeking LPSK protection, including provisions regarding research-based reporting. In Indonesia, individuals who disclose corruption cases as witnesses or "whistleblowers" and provide clear information regarding illicit activities, particularly those related to organized crime, may be granted legal protection. The aforementioned safeguards can be inferred from the Witness and Victim Protection Law Number 31 of 2014. The group passed Law No. 31 of 2014 which regulates the legal framework and reporting procedures for those with knowledge of corruption crimes in Indonesia, as well as the protection of witnesses and victims, after much deliberation.